The Federal Democratic Republic of Ethiopia : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for The Federal Democratic Republic of Ethiopia. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This 2016 Article IV Consultation highlights that Ethiopia's macroeconomic outturn during 2015/16 has been adversely affected by a severe drought and the weak global environment. As a result, output growth is estimated to have slowed down to 6.5 percent in 2015/16. The slowdown was mitigated by effective and timely policy responses to the drought, and buoyant industrial and services sectors. Over the medium-term, growth is projected to recover to within the 7.3-7.5 percent range, reflecting the growth-oriented reforms envisaged in the recently adopted second Growth and Transformation Plan. Public investment is projected to moderate, while private investment is projected to increase gradually.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet